Penerapan Model Pembelajaran Kooperatif Tipe Teams Game Tournament Terhadap Hasil Belajar Bimbingan TIK - Putra, Dino Adi; Refdinal, Refdinal; Edidas, Edidas; Fadhilah, Fadhilah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to determine the effectiveness of the application of the Teams Game Tournament (TGT) Cooperative Learning Model on ICT Guidance Learning Outcomes at UPT SMP N 2 Painan. The type of research used is experimental research. This research uses numerical research procedures and the analysis uses statistics and uses quantitative methods. For the research results, the experimental class data is 78.933 with the control class average score is 69.76. The final test analysis where the tcount is 9.484 and ttable is 1.68 with a 95% significance level so that tcount > ttable, the research hypothesis is accepted. For student activity and response, the average result is 4,301 with a percentage of 86,037 with a very good classification and for the average student response result is 4,343 with a percentage of 86,871 with a very good classification. The effectiveness of the TGT learning model in the effectiveness trial, it was found that 87% of students got a score of 70 which was classically effective and for the control class, 43.33% of students got a score of <70 which was not classically effective. In terms of Gain Score, it gets a value of 37.31% (medium). In conclusion, there is an effect of the Team Game Tournament (TGT) cooperative learning model on student learning outcomes.